2012
DOI: 10.1371/journal.pone.0038214
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Is a Potential Biomarker for Severe Pandemic H1N1 Influenza A Infection

Abstract: Pandemic H1N1 influenza A (H1N1pdm) is currently a dominant circulating influenza strain worldwide. Severe cases of H1N1pdm infection are characterized by prolonged activation of the immune response, yet the specific role of inflammatory mediators in disease is poorly understood. The inflammatory cytokine IL-6 has been implicated in both seasonal and severe pandemic H1N1 influenza A (H1N1pdm) infection. Here, we investigated the role of IL-6 in severe H1N1pdm infection. We found IL-6 to be an important feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 40 publications
5
107
0
7
Order By: Relevance
“…IL-6 in the airway samples could derive from monocytes, T cells, and/or airway cells (38). The role of IL-6 in ALI is not defined; however, IL-6 has been associated with increased disease severity in enteroviral (39) and human influenza infections (40,41), and could contribute to the overall inflammatory process, leading to lung injury as a result of the virus infection.…”
Section: Cd8mentioning
confidence: 99%
“…IL-6 in the airway samples could derive from monocytes, T cells, and/or airway cells (38). The role of IL-6 in ALI is not defined; however, IL-6 has been associated with increased disease severity in enteroviral (39) and human influenza infections (40,41), and could contribute to the overall inflammatory process, leading to lung injury as a result of the virus infection.…”
Section: Cd8mentioning
confidence: 99%
“…Effector cells such as macrophages, neutrophils and NK cells are recruited into the lungs as part of the innate immune responses [14]; here, histopathological examination showed that the deficit of CXCL14 did not alter the localization of the inflammatory infiltrate and its extent was neither increased or diminished ( Figure 2C). Despite the local upregulation of CXCL14 during viral infection [12], CXCL14 does not seem to have a pivotal role in regulating the inflammation in the lung, a process that is governed by a different subset of cytokines and chemokines.…”
Section: Cxcl14 Deficiency Does Not Impact the Outcome Of Influenza Imentioning
confidence: 98%
“…another study published by our group, microarray analysis revealed the presence of different chemokines in the lungs of mice infected with influenza, including CXCL9, CXCL10 and CXCL14 (Gene Expression Omnibus accession GSE31022) [12]. While abundant biological information is available for CXCL9 and CXCL10 [13], only limited information is available about the role of CXCL14 in the context of infectious diseases.…”
Section: Cxcl14 Deficiency Does Not Impact the Outcome Of Influenza Imentioning
confidence: 99%
“…Было отобрано пять исследований, отве-чающих критерию включения/невключения научных работ [4,5,7,8,10]. В таблицу 1 сведе-но число пациентов в данных исследованиях, на которой видно, что выбранные исследова-ния по числу пациентов достаточно однородны: среднее число пациентов, округленное до цело-го -М = 33; среднеквадратическое отклоне-ние -σ = 7,71; коэффициент вариации -K = М/σ = 0,23 (≤ 1).…”
Section: результатыunclassified
“…Среди большого числа провоспалительных цитокинов в качестве ведущего участника ци-токинового шторма при гриппе ряд авторов указывает на IL-6, повышенный уровень кото-рого отмечался именно при тяжелом течении гриппа как в экспериментальных условиях [12], так и в периферической крови больных [4,5,7,8,10,11]. Так из 6 цитокинов воспаления (TNFα, IL-1β, IL-6, IL-8, IL-17 и IFNγ) в перифериче-ской крови больных тяжелой формой гриппа А(H1N1)pdm09 наиболее резким (в 20 раз выше нормы) было повышение уровня IL-6 [5].…”
unclassified